1979
DOI: 10.6028/nbs.bss.120
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for stair safety

Abstract: Locating Alternate Means of Vertical Movement .. 2.7.2 Orientation of User to Stair Destination 2.7.3 Entries to Locked Fire Stairs 2.7.4 Essential Facilities at Each Level for the Elderly or Handicapped 2.7.5 Cues on Walls and Ceilings to Mark Beginning and Ending of Stairs 2.7.6 Non-Visual Cues for Handicapped and Elderly Users at Entrances to and Exits From Stairs . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 8 publications
1
46
0
Order By: Relevance
“…The recommendations from these studies are for risers to have a maximum height of 180 mm (7 in) and runs to have a minimum length of 280 mm (11 in). Archea et al (1979) report that one of the most prevalent stair fall scenarios involves tripping over or stepping past one-and tworiser stairs and encroachments. Templer et al (1978) report that, in addition to other factors, more missteps were observed to occur on shorter flights than on longer ones.…”
Section: Stair Steepnessmentioning
confidence: 98%
“…The recommendations from these studies are for risers to have a maximum height of 180 mm (7 in) and runs to have a minimum length of 280 mm (11 in). Archea et al (1979) report that one of the most prevalent stair fall scenarios involves tripping over or stepping past one-and tworiser stairs and encroachments. Templer et al (1978) report that, in addition to other factors, more missteps were observed to occur on shorter flights than on longer ones.…”
Section: Stair Steepnessmentioning
confidence: 98%
“…Aside from the ethical difficulties of recording stair usage in public or private spaces, there is a technical difficulty imposed by the rarity of adverse events. It is estimated that on public staircases, a slip, stumble, trip, or other loss of balance not resulting in a fall occurs once in 2222 stair uses, while minor accidents such as falls occur only once in 63,000 stair uses [5]. It is hypothesized that the labour intensive process of manually identifying unusual events in stair video data can be avoided with an automated system which is proposed herein.…”
Section: Introductionmentioning
confidence: 99%
“…There are two synergistic approaches to stair safety--accident reduction and injury limitation. The former has been the focus of almost all the reported studies to date (Archea, 1979;Templer, 1989). We have learned from these studies how to reduce the incidence of stair falls by improved design, maintenance, and user behavior.…”
mentioning
confidence: 95%
“…The staircase is undoubtedly the locus of many accidents. It has been estimated that in 1986, in the U.S., nearly 800,000 people received hospital treatment for injuries resulting from stair accidents, and about 32,000 were hospitalized (U.S.Consumer Product Safety Commission,1986); from similar data from 1976, approximately 4,000 died (Archea, 1979). Stair accidents which are serious enough to disable the victim after the day of the fall amount to between 1,800,000 and 2,660,000 per year.…”
mentioning
confidence: 98%